1994
DOI: 10.1002/hep.1840200602
|View full text |Cite
|
Sign up to set email alerts
|

Significance of IgG and IgM HCV antibody secretion in vitro in patients with chronic hepatitis C: Correlation with disease activity and response to interferon-α

Abstract: Hepatitis C virus antibodies are found in the serum of most patients with chronic hepatitis C. However, the significance of the humoral response is still uncertain. In this study, in vitro IgG and IgM anti-hepatitis C virus secretion by peripheral blood mononuclear cells of patients with chronic hepatitis C was analyzed. Peripheral-blood mononuclear cells from 21 of 36 patients (58.3%) secreted IgG anti-hepatitis C virus in vitro, as demonstrated with anti-hepatitis C virus-specific enzyme immunoassays and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Comparison of untreated and treated non-responders patients showed clearly that treatment with IFNa and/or ribavirin suppresses the anti-HCV antibodies secretion in vitro. We could not find any secretion in responders and long-term responders in accordance with Lohr et al [1994] which showed that the HCV antibody-negative patients were mostly responders to IFNa therapy. It has been hypothesized that persistent antigenic stimulation is responsible for the production of HCV-specific antibodies by B lymphocytes in vitro.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Comparison of untreated and treated non-responders patients showed clearly that treatment with IFNa and/or ribavirin suppresses the anti-HCV antibodies secretion in vitro. We could not find any secretion in responders and long-term responders in accordance with Lohr et al [1994] which showed that the HCV antibody-negative patients were mostly responders to IFNa therapy. It has been hypothesized that persistent antigenic stimulation is responsible for the production of HCV-specific antibodies by B lymphocytes in vitro.…”
Section: Discussionsupporting
confidence: 91%
“…Specific antibody secretion in vitro was demonstrated in patients with chronic hepatitis C, although differences in the level of production were observed [Ducos et al, 1994;Lohr et al, 1994;Quinty et al, 1995]. Comparison of untreated and treated non-responders patients showed clearly that treatment with IFNa and/or ribavirin suppresses the anti-HCV antibodies secretion in vitro.…”
Section: Discussionmentioning
confidence: 96%
“…We have also developed and evaluated the ELISpot assay for detecting anti‐HCV IgM‐secreting B cells. It has been reported that IgM anti‐HCV in serum might be predictive of viral clearance in acute hepatitis C or response to interferon therapy 36–40. However, these results have been controversial and other studies have shown a significant correlation between IgM anti‐HCV levels in serum and the recurrence of hepatitis C after liver transplantation 41, 42.…”
Section: Discussionmentioning
confidence: 99%